Working to learn : transforming learning in the workplace - Evans, Karen, 1949-; Hodkinson, Phil; Unwin, Lorna (Kogan Page ; Stylus Pub., 2002)
International in scope, Working to Learn brings together acknowledged experts in this field. Taking both evidence-based and analytical perspectives, the book challenges many of the generalizations about the changing nature of work and skills, and identifies the workplace itself a critical site for access to learning. In doing so, it develops an illuminating perspective on the social context of the modern workplace and highlights the implications of change for management, for the regulat.